What a girl wants - Gordon, Dennie; Warner Bro's (United States Warner Bros. Pictures, 2003)
An American teenager travels to England to meet her aristocratic father for the first time and discovers the challenges of fitting into high society while staying true to herself.
Originally released as a motion picture in 2003.
MPAA rating: PG.
Keywords: Fathers and daughters; Teenagers $v Drama; Aristocracy (Social class)